Integration of Digital Literacy into the Development of Students' Science Process Skills in Straight Line Motion Dynamics - Darmaji, Darmaji; Astalini, Astalini; yusnidar, Yusnidar; Kurniawan, Dwi Agus; Sri Wina Oktavia; Elza Triani; Rahmat Perdana (Universitas Muhammadiyah Makassar, 2026)
The integration of digital literacy into physics education is becoming increasingly important as students need to access, evaluate, interpret, and utilize digital information for scientific inquiry. This study examined the impact of digital literacy on students’ science process skills in learning straight-line motion dynamics and how digital tools support experimental activities. A mixed methods design with an explanatory sequential approach was used. Quantitative data were collected from 40 grade XI students at SMA Negeri 11 and SMA Negeri 12 in Jambi City using a digital literacy questionnaire and a science process skills observation sheet. The questionnaire assessed technical, cognitive, and ethical competencies in the use of digital technology, while the observation sheet evaluated skills such as observing motion phenomena, hypothesizing, identifying variables, designing experiments, analyzing data, interpreting kinematic graphs, and drawing conclusions. Qualitative data were collected through semi-structured interviews with selected students to contextualize the quantitative findings. Data analysis included normality and linearity tests, followed by simple linear regression using SPSS 25.0 for quantitative data, and Miles and Huberman’s interactive model for qualitative analysis. Results demonstrated that digital literacy significantly influences students’ science process skills, with a p-value of 0.000 (< 0.05). The R-square value of 0.523 indicated that digital literacy explained 52.3% of the variation in science process skills. Interviews revealed that digital tools such as PhET simulations, motion analysis apps, instructional videos, sensors, and digital graphs helped students understand uniform and accelerated motion more concretely. This study's novelty lies in positioning digital literacy as an active, measurable component of straight-line motion learning rather than just supplementary media. It concludes that systematically integrating digital literacy can enhance students’ science process skills and supports the development of technology-supported inquiry learning in secondary physics education.